1
$\begingroup$

Problem: convolution ($f*g) $ of functions $f,g\in L^1([0,1])$, where:

$$f(x) = \frac{3}{5-4\cos{4\pi x}},$$ $$g(x) = \frac{2\cos{2\pi x}}{5-4\cos{4\pi x}},$$

and $$(f * g)(x) = \int_{0}^{1}f(x-y)g(y)dy.$$

I'm not sure how to approach this problem. This is a problem from a course dealing with Fourier Analysis and I'm working in $[0,1]$ where Fourier series of functions are of the form $$\sum_{n \in\mathbb{Z}} f_c(n) e^{2\pi i nx}$$

where $f_c(n)=\int_{0}^1 f(x)e^{-2\pi i nx}dx.$

What I know is $(f*g)_c (n) = f_c(n)g_c(n),$ but I'm not sure if this would help. We haven't yet dealt with the question of whether a Fourier series converges to the function, unless $f$ is literally equal to the Fourier series itself though, so I'm not sure if that would be helpful at all.

I also know the result is $0$, and direct integration hasn't yielded any results.

Any hints would be appreciated!

$\endgroup$
2
$\begingroup$

First note a couple of translation symmetries: $$ f(x-1/2) = \frac{3}{5-4\cos{4\pi (x-1/2)}} = \frac{3}{5-4\cos{4\pi x}} = f(x) \\ g(x+1/2) = \frac{2\cos{2\pi (x+1/2)}}{5-4\cos{4\pi (x+1/2)}} = \frac{-2\cos{2\pi x}}{5-4\cos{4\pi x}} = -g(x+1/2) $$

Then we split the integral into two parts and translate the second one: $$\begin{align} (f * g)(x) &= \int_{0}^{1} f(x-y) \, g(y) \, dy \\ &= \int_{0}^{1/2} f(x-y) \, g(y) \, dy + \int_{1/2}^{1} f(x-y) \, g(y) \, dy \\ &= \{ z := y - 1/2 \} \\ &= \int_{0}^{1/2} f(x-y) \, g(y) \, dy + \int_{0}^{1/2} f(x-z-1/2) \, g(z+1/2) \, dz \\ &= \int_{0}^{1/2} f(x-y) \, g(y) \, dy + \int_{0}^{1/2} f(x-z) \, (-g(z)) \, dz \\ &= 0. \end{align}$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.